Merging and Demerging Education Ministries in Malaysia - Sack, Richard; Jalloun, Omar (International Higher Education, 2017)
There is little research about the potential effects of large-scale institutional changes. Mergers and demergers of educational ministries provide an example of such changes, with their impact on the detailed workings of the organizational mechanics of education systems. The case study reported here is based on the perceptions of the frontline actors concerned by mergers/demergers, none of whom expressed enthusiasm for the merger. Overall, the Malaysian merger, and the demerger two years later, had little overall effect. The short time of the merger was a factor, as well as the existence of autonomous agencies assuring key functions.